4P’s marketing strategy affecting customer’s purchase intentions towards Maxis / Siti Zaharah Salleh - Salleh, Siti Zaharah (2009)
The purpose of this study was to assist Maxis Communications in determining their services marketing mix. It is to identify the current strategies that have been practiced by Maxis Communications in term of the 4P’s. The research is also focusing on the perception of the customers towards the strategy that have been practiced by Maxis Communications to induce the customer’s suggestion and ideas on how Maxis can improve their performance to attract new customers and retain old customers. The results indicate that the product/services and the prices factor explained the highest proportion of customer’s purchase intention towards Maxis Communications. The weakness link in the 4P’s marketing strategy would be the promotional activities and the places where customer can reached their product are not aggressively and accurately performed in order to create customer awareness and enhance customer’s satisfaction. The researcher used descriptive research in order to conduct the research on the issue. Descriptive research is a type of conclusive research that has its major objective. 100 questionnaires were distributed to customers of Maxis and these respondents were selected using simple random sampling technique. Where the researcher distribute the questionnaire at Malacca Tengah. Questionnaires were distributed as the source of primary data. And the data obtained was processed and analyzed using the statistical package for social science (SPSS) version 14. The researcher also conducts several sessions of interview with the management of Maxis to gain the information relevant to achieve the objectives.